Web site implementation and usability among selected Malaysian financial firms - Khairul Akmaliah Adham; Maisarah Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2003)
Successful implementation of outwardly targeted corporate business web sites depends on their acceptance by customers. Prior research determined that such acceptance is influenced by a number of variables, including the presence of certain content and design features. However, it was not known whether Malaysian firms in the financial sector incorporated these features into their web sites. This study selected a sample of 65 companies classified under the financial sector in the Kuala Lumpur Stock Exchange (KLSE) main board listings. First, the researchers ascertained whether these firms did indeed have outwardly targeted corporate web sites that were operable. Second, the operable web sites were evaluated according to the Usability Assessment Guide, which was developed based on recognized, research- based standards. Results showed that 35 out of 65 of the firms (54%) had operable web sites, higher than that recorded in the UK, but lower than that found in the US, in similar studies. Rating of the firms' web sites revealed that the overall top scorer was MIDF (78%), followed by Bank Islam and RHB Bank, tied at 75%. Frequency counts of each usability variable revealed, among other things, that 100% of the firms had incorporated eight of the 28 Design variables and two of the 25 Content variables in their web sites. The Usability Assessment Guide can be used by firms in examining the usability of their own web sites, as well as the web sites of their competitors. Web sites that show high usability ratings can serve as benchmarks for others, and those with low ratings can be improved by upgrading them to the usability standards developed.